Perhitungan Burn Up pada Reaktor HCLWR Model Geometri Heksagonal Dua Dimensi BahanBakar Uranium menggunakan SRAC COREBN - Wahyuning Ramadhanta Ardanti; Yanti Yulianti; Agus Riyanto; Syafriadi Syafriadi (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2020)
This study about burn up calculations on the HCLWR reactor with two dimensional hexagonal geometric models of uranium using SRAC COREBN has been carried. This study used uranium-235 and uranium-238 as the fuels, light water as coolant and moderator. The calculation was done with computational simulation of COREBN. The calculation aims to produce a conversion ratio more than 1 and a critical multiplication factor (keff). The research used fuels enrichment, burn up period, burn up step, linier power and volume fraction parameters. The percentage of enrichment from U1 and U3 were 3% and U2 was 2,5%. The volume fraction of each material was 52% fuels, 12% cladding, and 36% coolant, the reactor operating period for 548 days with 6 step of burn up then the reactorpower is 2400 MW and the linear poweris 1,792722 MW/cm. The calculation of conversion ratio was 1,01233 and keff was 0,901.